Design and Build Integrated Water Filter Automation for Android Smartphones (IoT): Rancang Bangun Otomasi Filter Air Terintegrasi Smartphone Android (IoT) - Septiyan, Moch. Dani; Anshory, Izza; Ahfas, Akhmad; Jamaaluddin, Jamaaluddin (Indonesian Journal of Innovation Studies, 2021)
In the internet of things, one of the current developments is smartphone-based water automation which makes it easier for users to control water. The working principle of this research is the water contained in the water storage tank if the water level is below 25 cm then the water pump (water input) will be active until the water is above 25 cm. Then the solenoid valve (water output) can be opened and closed via the Blynk application. When the solenoid is opened, the water in the holding tank will pass through filters 1 and 2 into the filter reservoir. The water in the filtered reservoir will measure the level of acidity and turbidity and then display it on the Blynk application. The results of this study, the water filter can reduce the level of turbidity of water by 0.568 NTU and increase the level of acidity by 0.132. The PH sensor used has an accuracy rate of 93.53%. The Turbidity sensor or turbidity has an average of 1.00 NTU in measuring clean water (Aqua).